Solar radiation exposure of dihydrobiopterin and biopterin in aqueous solution - Ipiña Hernandez, Adriana (2014)
Dihydrobiopterin (H2Bip) and biopterin (Bip) accumulate in the skin of patients suffering from vitiligo, whose lack of melanin causes a deficient protection against UV radiation. H2Bip and Bip undergo photooxidation upon UV irradiation and the former acts as a photosensitizer of biomolecules. The aim of this work is to study the photochemical reactions of these compounds triggered by sunlight under outdoor conditions. H2Bip and Bip in aqueous solutions were exposed to sunlight in La Plata city (34.90°S, 57.92°W) from Spring equinox to near Summer solstice and the spectral solar irradiance was recorded with a high-resolution spectrometer. The photochemical reactions were followed by HPLC and UV-Vis spectrophotometry. Upon sun exposure, excitation of H2Bip leads to the formation of dimers and to its oxidation to Bip, which, in turn, is photooxidized into 6-formylpterin (Fop). Further excitation induces the oxidation of Fop to 6-carboxypterin, which is much more photostable than Bip and Fop and then it is accumulated in the solution. Rates of reactant consumption were determined under different weather conditions and the corresponding quantum yields were also calculated. We have demonstrated that solar radiation causes significant oxidation of the pterin derivatives investigated within a few minutes, even in cloudy days. Finally, the biological implications of our results are discussed.